HOCl as a Promising Candidate for Effective Containment of Covid 19 From Biological and Non-Biological Surfaces - Shukla, Sandeep K.; Sharma, Ajay Kumar; Kalonia, Aman; Shaw, Priyanka (Coronaviruses, 2022)
Covid 19 is a pandemic disease spread almost in the whole world. To date, no medical advancement to curb the virus. Coronavirus is an enveloped virus transmitted from the biological and non-biological surface by direct or indirect contact. Limited literature revealed that the enveloped virus can be killed by disinfectants. There are many biocidal agents used for decontamination of the virus, yet they have many issues like toxicity, killing time, activation requirement, etc. Some are specific to the inanimate surface but not used by a human being. This current situation showed an urgent need for a biocidal agent which can act on biological as well as non-biological surfaces without any potential toxicity. Moreover, it should be easy to handle, inexpensive, and safe for the environment. Hypochlorous acid is a weak acid that acts as a powerful disinfectant and shows biocidal efficacy against a wide range of microorganisms. Hypochlorous acid is simple to use, inexpensive, eco-friendly, non-toxic, and stable. The properties of HOCl can be regulated at the site of preparation and therefore, its compliance is high. Hypochlorous acid seems to be a promising agent in disinfection and sterilization in healthcare facilities. Due to its diverse biocidal actions, it may be used as a potent disinfectant against novel coronavirus.
Keywords: HOCL